Logbook: An Alternative Learning Media for Writing News Texts: - Azizah, Nurul; Chandra, Muhammad Rizky; Alfalah, Adib (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to investigate the effectiveness of using logbook media in teaching news text writing. The research was conducted at the beginning of the odd semester in the 2024/2025 academic year. The population consisted of seventh-grade students at SMP Nurul Hadina, and the sample involved 21 students from class VII Al Muqtadir. This study employed a quasi-experimental method. The research instrument used was an essay test on news text writing. The Wilcoxon Signed Rank Test showed a significance value of 0.001 < 0.05. This result indicates a significant difference between students’ scores before and after using logbook media in the news text writing learning process. Based on these findings, it can be concluded that the use of logbook media is an effective alternative tool in teaching news text writing.